2017
DOI: 10.1111/jpm.12441
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative experiences of disengagement in assertive outreach teams, in particular for “black” men: Clinicians’ perspectives

Abstract: Introduction Engagement with services is often poor amongst people with severe mental health problems, yet key to improving clinical outcomes. Aims This study explores the perception of clinicians on patients with severe mental health problems, in particular the experiences of black men, who disengage from mental health services. Method Two focus groups consisting of a combined total of twelve, mainly white, experienced clinicians in the UK were recruited. Transcripts were analysed using interpretative phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Codes were clustered and interpretative themes were generated from the codes and text; subsequently, these themes were dialectically related to excerpts of the text in a cyclical process. The process of data analysis was as reflective as possible and included interpretation from the researchers upon the emergent themes (Wagstaff et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Codes were clustered and interpretative themes were generated from the codes and text; subsequently, these themes were dialectically related to excerpts of the text in a cyclical process. The process of data analysis was as reflective as possible and included interpretation from the researchers upon the emergent themes (Wagstaff et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The time factor and need for continuity of contact with professional carers have been noted within the literature. A study researching clinician perspectives on men who identified as “Black” found that the clinicians perceived the therapeutic relationship as improving over time 27…”
Section: Discussionmentioning
confidence: 99%